PENERAPAN MODEL BLENDED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEPTUAL DAN KELANCARAN PROSEDURAL SISWA PADA MATERI STATISTIKA KELAS VIII - Maya Puspita Artasari; Ahmad Yani T; Dona Fitriawan; Edy Yusmin; Romal Ijuddin (STKIP Singkawang, 2022)
This research aims to find the effect of applying the blended learning model to increase students' conceptual understanding and procedural fluency in statistics material in junior high schools. The Blended Learning model is used to with flipped classroom sub-model. This type of sub-model has two classes, named online and offline. For online's classes, use the help of the WhatsApp application and Google Classroom. The application of this blended learning model are expect to improve students' conceptual understanding and procedural fluency in learning mathematics, especially in statistical's subject matter to be researched in this research. This research is a type of quantitative research using experimental methods. Data collection techniques that used in this research is observation and tests. The observation in question is the teacher's observation using the observation sheet to observe the teacher's activities in teaching when the question test is a test of conceptual understanding and procedural fluency in the form of an essay test. Data analysis techniques were performed with calculating the results of the pretest and posttest in the experimental class and control class and then carrying out a Test of Normality, Test of Homogeneity of Variance, Paired Sample Test, Independent Sample Test, and concluding the results of the test. The results of the research are that both the blended learning model and the conventional learning model both have an increase. Even though there is an increase in both the blended learning model and the conventional learning model does not have a significant effect on students' conceptual understanding and procedural fluency even though the results show that there is a difference in the increase between the experimental class and the control class.